„Żyć z…, żyć dla…” Rozmowa z Alicją Kapuścińską o jej życiu z mężem podróżnikiem - Sumińska, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Mrs Alicja Kapuscinska presents a story of her life that she shared with her husband – traveller. She talks about her day-to-day life and how it was affected by all the journeys he took. She brings up her memories of the first trips her husband went for and the way he was preparing for them, all the successes and worries related to them. In her story she includes all the difficult situations, illnesses and hard decisions that needed to be taken that would affect their whole life. She talks in simple words about all the values that lead her husband in his life. She portrays the process of her husband attaining one goal after another and, first of all, how he has become a wonderful writer and reporter recognised all over the world.